Experimental design of hair sampling: Preparation of hair specimens for taxonomic identification using microscopic morphology - Bisan, Kirati; Hasin, Sasitorn (Asian Science and Technology Innovation Journal, 2025)
Hair morphology provides important class-level information for mammalian species identification in forensic investigations, wildlife law enforcement, and museum-based taxonomy, particularly when biological material is limited or unsuitable for DNA analysis. This study presents a standardised experimental design for hair sampling and preparation to improve the reliability and reproducibility of microscopic hair examinations. The protocol evaluates detergent- and solvent-based cleaning methods, permanent slide mounting, cuticular cast preparation, and transverse cross-sectional analysis to examine diagnostic features of the cuticle, cortex, and medulla. Quantitative morphometric measurements were obtained from standardised mid-shaft regions, while cross-sectional analysis was used to assess internal structure and pigment distribution. Emphasis is placed on methodological standardisation, defined measurement criteria, and interpretation within a class-level framework consistent with accepted forensic principles. The proposed workflow enhances transparency and comparability in hair morphology analysis. It provides a practical foundation for forensic casework, wildlife forensic investigations, and the development of reference collections, particularly in biodiversity-rich regions where non-invasive sampling is essential.